Severity of Fallot’s tetralogy and its relationship to electrocardiographic observations - Onat, Altan; Onat, Teoman (The Turkish Journal of Pediatrics, 1966)
Electrocardiographic observations were investigated in the cases of 84 cyanotic patients with Fallot’s tetralogy in which the pulmonary blood flow was reduced to varying extents to find the relationship to the degree of severity of the disease. The voltage of R waves and the R/S ratio in leads V_5 and V_6 showed an inverse relationship to the severity grade (p < 0.001). On the other hand, no parallel was noted between the R amplitude and R/S ratio in lead V_1, conventional criteria of right ventricular hypertrophy. Optimal electrocardiographic criteria were presented which aid in differentiating «mild» from «severe» cases of the tetralogy. The specificity and sensitivity rates of these criteria were found to be high enough to justify their practical use. The observations in left - sided precordial leads demonstrated a tendency to regress following systemic - pulmonary anastomosis, a procedure which, by increasing the pulmonary blood flow, promotes left ventricular filling without reducing the pressure load of the right ventricle.